PENYELESAIAN PERKARA PIDANA DENGAN KONSEP KEADILAN RESTORATIF (RESTORATIVE JUSTICE) DALAM SISTEM PERADILAN PIDANA TERPADU DI INDONESIA - Kristian Kristian; Christine Tanuwijaya (Universitas Suryakancana, 2015)
Various problems that occur in a community, is a social phenomenon that has existed since the start of human life. Problem solving methods that can be taken is basically divided into two, namely the completion of the litigation and non-litigation pathway. In fact, if there is a problem, especially with regard to criminal law (criminal case), the model of problem solving is always done using the path of litigation. The settlement of this litigation by using paths in practice does not always go according to what is expected due to the settlement of litigation by using the path in the traditional criminal justice system today would lead to new problems such as: pattern of retaliatory punishment still, causing a buildup of the case, do not pay attention to the rights of the victim, not in accordance with the principle of simple justice; process is long, complicated and expensive, and the settlement is legistis stiff, does not restore the effects of crime, prisons conditions are not adequate, does not reflect justice for the community and so although, the law was made essentially to provide fairness and benefits to humans. Looking at these phenomena, in the latest development emerged a new concept or approach the concept of restorative justice. The concept of restorative justice approaches assessed or can cope with various problems in the traditional criminal justice system as mentioned above.This study will discuss the application of restorative justice in terms of the integrated criminal justice system in Indonesia. This research is a descriptive normative legal analysis. The approach used is a statutory approach, conceptual approach, and the principles of law.Keywords: Restorative Justice, Integrated Criminal Justice System.